Quality of Work Life as a Predictor of Work Engagement in Generation Z Employees - Aysila, Andi Fenita; Kusmaryani , Rosita Endang (LifeSciFi, 2025)
Generation Z, characterized by their preference for meaningful work, increasingly dominates the workforce in non-governmental organizations in Indonesia. Quality of work life is critical for fostering work engagement in this demographic, yet its impact remains underexplored in the non-governmental organization’s context. This study investigates the influence of quality of work life, based on Walton’s model, on work engagement among Generation Z employees in Indonesian non-governmental organizations. A quantitative survey design was employed, involving 286 Generation Z employees selected through accidental sampling. Data was collected using the Utrecht work engagement scale and a quality of work life scale adapted from Walton’s framework, analyzed via multiple linear regression with SPSS version 25. The findings reveal that quality of work life significantly predicts work engagement, with constitutionalism and total life space (13.73% contribution) as the most influential dimensions, supporting the hypothesis that quality of work life enhances engagement. Quality of work life plays a pivotal role in fostering vigor, dedication, and absorption among Generation Z in non-governmental organizations, confirming its importance in mission-driven settings. This study extends Walton’s quality of work life model to a new demographic and context, offering practical insights for non-governmental organizations to enhance engagement through fair policies and work-life balance initiatives.